Novel high strength PVA/soy protein isolate composite hydrogels and their properties - Zhao, Yanteng; Jin, Lu; Liu, Xin; Liu, Xue; Dong, Shuling; Chen, Yun; Li, Xianyu; Lv, Xianping; He, Meng (Frontiers in Chemistry, 2022)
High strength polyvinyl alcohol (PVA)/soy protein isolate (SPI) composite hydrogels (EPSG) were constructed by the introduction of PVA into SPI through the crosslinking with epichlorohydrin (ECH) and a freezing-thawing process. The EPSG hydrogels were characterized by scanning electron microscopy, FTIR, X-ray diffraction and compressive test. The results revealed that chemical crosslinking interactions occurred for SPI and PVA during the fabrication process. The composite hydrogels exhibited a homogenous porous structure, indicating certain miscibility between PVA and SPI. The introduction of PVA increased the compressive strength of SPI hydrogels greatly, which could reach as high as 5.38 MPa with the water content ratio of 89.5%. Moreover, the water uptake ratio of completely dried SPI hydrogel (namely xerogel) decreased gradually from 327.4% to 148.1% with the incorporation of PVA, showing a better potential as implants. The cytocompatibility and hemocompatibility of the EPSG hydrogels were evaluated by a series of in vitro experiments. The results showed that the EPSG hydrogels had no cytotoxicity (cell viability values were above 86.7%), good biocompatibility and hemocompatibility, showing potential applications as a direct blood contact material in the field of tissue engineering.